Ves' sornyak dolzhny vypolot' my bez ostatka - Aminadav, Kanevsky (ОГИЗ - ИЗОГИЗ (Izogiz), 1933)
Collective farmer pulling up weeds taking the form of counter-revolutionary figures, the largest labelled Kulak Original title: Весорняк долгий выполет моя без остатка. Suggested translation: We must weed out the whole weed without residue PO-0034